Fixational eye movements abnormalities and rate of visual acuity and stereoacuity improvement with part time patching - Scaramuzzi, Matteo (Sci Rep, 2021)
Residual amblyopia is seen in 40% of amblyopic patients treated with part-time patching. Amblyopic patients with infantile onset strabismus or anisometropia can develop fusion maldevelopment nystagmus syndrome (FMNS). The purpose of this study was to understand the effects of presence of FMNS and clinical subtype of amblyopia on visual acuity and stereo-acuity improvement in children treated with part-time patching. Forty amblyopic children who had fixation eye movement recordings and at least 12 months of follow-up after initiating part-time patching were included. We classified amblyopic subjects per the fixational eye movements characteristics into those without any nystagmus, those with FMNS and patients with nystagmus without any structural anomalies that do not meet the criteria of FMNS or idiopathic infantile nystagmus. We also classified the patients per the clinical type of amblyopia. Patching was continued until amblyopia was resolved or no visual acuity improvement was noted at two consecutive visits. Children with anisometropic amblyopia and without FMNS have a faster improvement and plateaued sooner. Regression was only seen in patients with strabismic/mixed amblyopia particularly those with FMNS. Patients with FMNS had improvement in visual acuity but poor stereopsis with part-time patching and required longer duration of treatment.